Maths-

General

Easy

Question

# Use Substitution to solve each system of equations :

- 3X - Y = 7

X + 2Y = 6

Hint:

### find x by substituting y (in terms of x) in the equation and find y by substituting value of x in the equations.

## The correct answer is: ∴ x= -4 and y =5 is the solution of the given pair of equations.

### Ans :- x = -4; y = 5

Explanation :-

- 3x - y = 7 ⇒ - 3x - 7 = y — eq 1

x + 2y = 6 —- eq 2

x + 2 ( - 3x - 7) = 6 ⇒ x - 6x - 14 = 6

⇒ - 5x = 14 + 6 ⇒ - 5x = 20

⇒ x = -4

Step 2 :- substitute value of x and find y

⇒ - 3x - 7 = y ⇒ y = - 3 (- 4) - 7

⇒ y = 12 - 7

∴ y = 5

x = -4 and y = 5 is the solution of the given pair of equations.

### Related Questions to study

Maths-

### If Q is the midpoint of PR, prove that PR = 2 PQ.

Give a two-column proof.

### If Q is the midpoint of PR, prove that PR = 2 PQ.

Give a two-column proof.

Maths-General

Maths-

### Compare 𝑚∠𝑃𝑂𝑄𝑎𝑛𝑑∠𝑆𝑂𝑇.

### Compare 𝑚∠𝑃𝑂𝑄𝑎𝑛𝑑∠𝑆𝑂𝑇.

Maths-General

Maths-

### Which postulate will you use to prove that PR = PQ + QR?

### Which postulate will you use to prove that PR = PQ + QR?

Maths-General

Maths-

### Solve the system of equations by elimination :

X - 2Y = - 2

3X + 2Y = 30

### Solve the system of equations by elimination :

X - 2Y = - 2

3X + 2Y = 30

Maths-General

Maths-

### Solve the following by using the method of substitution

Y = 4X+2

Y = X+8

### Solve the following by using the method of substitution

Y = 4X+2

Y = X+8

Maths-General

Maths-

### If lines l and m are parallel, find the value of x.

### If lines l and m are parallel, find the value of x.

Maths-General

Maths-

Prove that: PR = PQ + QR

Give a two-column proof

Prove that: PR = PQ + QR

Give a two-column proof

Maths-General

Maths-

### Find x and hence find 𝑚∠𝐶𝑂𝐷

### Find x and hence find 𝑚∠𝐶𝑂𝐷

Maths-General

Maths-

### Solve the system of equations by elimination :

X - Y = 4

2X + Y = 5

### Solve the system of equations by elimination :

X - Y = 4

2X + Y = 5

Maths-General

Maths-

### Use Substitution to solve each system of equations :

X = -Y + 3

3X - 2Y = -1

### Use Substitution to solve each system of equations :

X = -Y + 3

3X - 2Y = -1

Maths-General

Maths-